Factors Influencing the Implementation of SIMRS at Mardi Waluyo Hospital - Tutus Fibri Ajimas Budi; Nurwijayanti Nurwijayanti; Agus Khoirul Anam; Andi Hayyun Abiddin (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Information System of Hospital Management (SIMRS) as a system that supports complexity of health services. This technology support is able to improve services of health which have an impact on the quality of a hospital. Many factors affect the use of SIMRS. The objectived of this study to identify the factors that influence the implementation of SIMRS in Mardi Waluyo Hospital, Blitar City. The research design was a cross sectional study, with a population of 291 nurses and midwives at Mardi Waluyo Regional Hospital, Blitar City. The sampling technique used Disproportionate Stratified Random Sampling to obtain a sample size of 168 subjects who met the inclusion criteria, namely working for more than 3 months, and the exclusion criteria: not willing to sign an informed consent. Data collection used Googleform media was undertake from January to February 2021. The research used simple linear regression analysis. The research results showed a relationship between leadership, organizational commitment and resistance to change towards optimizing the implementation of SIMRS with OR values (0,44; 0,14; and 0,21) respectively. Training on the use of SIMRS is very necessary, so that human resources (users of SIMRS) can improve their abilities optimally in using SIMRS. In addition, hospital management is expected to cooperate with SIMRS developers who are able to develop a SIMRS that is easy to operate so that the service quality to the community is increasing.